MusE GAs FLOw and Wind (MEGAFLOW) – III. Galactic wind properties using background quasars. Issue 3 (12th October 2019) - Schroetter, Ilane; Bouché, Nicolas F; Zabl, Johannes; Contini, Thierry; Wendt, Martin; Schaye, Joop; Mitchell, Peter; Muzahid, Sowgat; Marino, Raffaella A; Bacon, Roland; Lilly, Simon J; Richard, Johan; et al.
ABSTRACT: We present results from our on-going MusE GAs FLOw and Wind (MEGAFLOW) survey, which consists of 22 quasar lines of sight, each observed with the integral field unit MUSE and the UVES spectrograph at the ESO Very Large Telescopes (VLT). The goals of this survey are to study the properties of the circumgalactic medium around z ∼ 1 star-forming galaxies. The absorption-line selected survey consists of 79 strong Mg ii absorbers (with rest-frame equivalent width ≳0.3 Å) and, currently, 86 associated galaxies within 100 projected kpc of the quasar with stellar masses ( M ⋆ ) from 10 9 to 10 11 M⊙ . We find that the cool halo gas traced by Mg ii is not isotropically distributed around these galaxies from the strong bi-modal distribution in the azimuthal angle of the apparent location of the quasar with respect to the galaxy major axis. This supports a scenario in which outflows are bi-conical in nature and co-exist with a co-planar gaseous structure extending at least up to 60–80 kpc. Assuming that absorbers near the minor axis probe outflows, the current MEGAFLOW sample allowed us to select 26 galaxy–quasar pairs suitable for studying winds. From this sample, using a simple geometrical model, we find that the outflow velocity only exceeds the escape velocity when M ⋆ ≲ 4 × 10 9 M⊙, implying the cool material is likely to fall back except in the smallest haloes. Finally, we find that the mass loading factor η, the ratio between the ejected mass rate and the star formation rate, appears to be roughly constant with respect to the galaxy mass.